IMPLEMENTASI METODE V_SHAPE DALAM PERANCANGAN SISTEM INFORMASI INFLUENCER MARKETING - Alif Fahmi Sanjaya; Biktra Rudianto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
PT Dimensi Nirmana Semesta and is a company providing marketing communication services through digital platforms. One of the marketing strategies at PT Dimensi Nirmana Semesta on social media is to use influencer marketing. It's just that, choosing the right influencer to promote a product or service is not easy. If you choose the wrong influencer, this can affect the image of the business in the eyes of consumers. In addition, the results obtained may not be optimal because the influencer's performance is not optimal in promoting the product or service. The construction of an influencer marketing information system can assist business owners in choosing the right influencers to market products according to the type of product. The method used is object-oriented with structured web modeling, the diagram used is UML and the database uses MYSQL while the application is made using PHP programming with the help of the Laravel framework. And a web-based application program is produced that can make it easier to choose an influencer .